Formation of new crystalline qtz-[Zn(mIm)2] polymorph from amorphous ZIF-8. Issue 85 (7th October 2022) - Thorne, Michael F.; Castillo-Blas, Celia; McHugh, Lauren N.; Bumstead, Alice M.; Robertson, Georgina; Sapnik, Adam F.; Coates, Chloe S.; Sayed, Farheen N.; Grey, Clare P.; Keen, David A.; Etter, Martin; da Silva, Ivan; et al.
Abstract : Formation of a new crystalline qtz-[Zn(mIm)2 ] polymorph from amorphous ZIF-8. Abstract : The structure of a new ZIF-8 polymorph with quartz topology (qtz) is reported. This qtz-[Zn(mIm)2 ] phase was obtained by mechanically amorphising crystalline ZIF-8, before heating the resultant amorphous phase to between 282 and 316 °C. The high-temperature phase structure was obtained from powder X-ray diffraction, and its thermal behaviour, CO2 gas sorption properties and dye adsorption ability were investigated.